Peranan Sosial Media dalam Mengedukasi Generasi Muda Mengenai Literasi Keuangan untuk Membangun Kebiasaan Menabung - Rajagukguk, Richard Julianus; Susanti, Elizabeth (Ideas Publishing, 2024)
Good financial literacy can help someone understand the importance of saving and managing money wisely. This research aims to determine the level of financial literacy and the role of social media on the financial behavior of the younger generation. Data collection in this research used case study comparisons with secondary data from existing research journals. The research results show that the role of social media in educating financial literacy is still low compared to the negative influence of social media as a trigger for consumer behavior in the younger generation. The role of social media in educating the younger generation about financial literacy can positively impact efforts to prevent consumer behavior and increase the younger generations awareness of the importance of saving